Hidden Species Diversity was Explored in Two Genera of Catapyrenioid Lichens (Verrucariaceae, Ascomycota) from the Deserts of China - Tingting Zhang; Xin Zhang; Qiuxia Yang; Xinli Wei (Journal of Fungi, 2022)
Verrucariaceae is the third-largest lichen family with high species diversity. However, this diversity has not been well-explored in China. We carried out a wide-scale field investigation in the arid and semi-arid regions of Northwest China from 2017 to 2021. A large number of lichen groups, especially those commonly distributed in deserts, were collected. Based on molecular phylogeny using ITS and nuLSU sequences by Bayesian and maximum likelihood analyses, combining morphological characters, seven taxa of catapyrenioid lichens in Verricariaceae were found in this study, including one genus (Clavascidium) and one species (Clavascidium lacinulatum) new to China; one genus (Placidium) new to the mainland of China; and four species (Clavascidium sinense, Placidium nitidulum, Placidium nigrum, and Placidium varium) new to science. It enriched our understanding of the high species diversity in Verrucariaceae and the lichen flora of Chinese arid and semi-arid deserts.